ACE2 overexpression in corticotropin-releasing-hormone cells offers protection against pulmonary hypertension - Oliveira, Aline C.; Karas, Marianthi M.; Alves, Matthew; He, Jacky; de Kloet, Annette D.; Krause, Eric G.; Richards, Elaine M.; Bryant, Andrew J.; Raizada, Mohan K. (Frontiers in Neuroscience, 2023)
Pulmonary hypertension (PH), characterized by elevated pulmonary pressure and right heart failure, is a systemic disease involving inappropriate sympathetic activation and an impaired brain-lung axis. Global overexpression of angiotensin converting enzyme 2 (ACE2), a cardiopulmonary protective enzyme of the renin-angiotensin system, attenuates PH induced by chronic hypoxia. Neurons within the paraventricular nucleus of the hypothalamus (PVN) that synthesize corticotropin-releasing hormone (CRH) are activated by stressors, like hypoxia, and this activation augments sympathetic outflow. These data coupled with our observations that ACE2 overexpression in CRH cells (CRH-ACE2KI mice) decreases anxiety-like behavior by decreasing CRH synthesis, led us to hypothesize that selective ACE2 overexpression in CRH neurons would protect against hypoxia-induced PH. Methods: CRH-ACE2KI and WT male and female mice were exposed to chronic hypoxia (10%O2) or normoxia (21%O2) for 4 weeks in a ventilated chamber (n=7-9/group). Pulmonary hemodynamics were measured with Millar pressure catheters then tissues were collected for histological analyses. Results: Chronic hypoxia induced a significant increase in right ventricular (RV) systolic pressure (RVSP) in WT mice, which was not observed in CRH-ACE2KI mice. No significant differences were observed between male and female mice. Conclusion: Overexpression of ACE2 in CRH cells was protective against hypoxia-induced PH. Since the majority of expression of CRH is in the PVN and central nucleus of the amygdala (CeA) these data indicate that the protective effects of ACE2 are, at least in part, centrally mediated. This contributes to the systemic nature of PH disease and that CRH neurons may play an important role in PH.